Au@HgxCd1-xTe core@shell nanorods by sequential aqueous cation exchange for near-infrared photodetectors. (March 2019) - Li, Xinyuan; Iqbal, Muhammad Ahsan; Xu, Meng; Wang, Yi-Chi; Wang, Hongzhi; Ji, Muwei; Wan, Xiaodong; Slater, Thomas J.A.; Liu, Jia; Liu, Jiajia; Rong, Hongpan; Chen, Wenxing; et al.
Abstract: We have explored the synthesis of Au@Hgx Cd1-x Te core@shell nanorods by sequential aqueous cation exchange (ACE) for near-infrared photodetector application. A number of related Au@telluride core/shell nanorod structures were put forwarded, taking advantage of multi-step transformations through a binary and then a ternary phase for the telluride shells. The latter have a high degree of crystallinity thanks to the step-wise ACE method. The use of only trace amounts of Cd 2+ coordinated with tri- n -butylphosphine, assisted the phase transformation from an amorphous Ag2 Te shell to a highly crystalline Ag3 AuTe2 shell in the first stage; this was followed by a further cation exchange (CE) step with far higher Cd 2+ levels to fabricate a highly crystalline CdTe shell, and with an additional CE with Hg 2+ to convert it to a Hgx Cd1-x Te shell. The composition of the shell components and the well-controlled thickness of the shells enabled tunable surface plasmon resonance properties of the Au@telluride nanorods in the NIR region. Utilizing the enhanced NIR absorption, a hybrid photodetector structure of Au@Hgx Cd1-x Te nanorods on graphene was fabricated, showing visible to NIR (vis-NIR) broadband detection with high photoresponsivity (~10 6 A/W). Graphical abstract: fx1 Highlights: New routes to Au@telluride core/shell nanorods by multi-step transformations. High degree of crystallinity shells realized by step-wise aqueous cation exchange. Au@Hgx Cd1-x Te (Au@Ag3 AuTe2 ) nanorods show tunable SPR property in vis-NIR region. Au@Hgx Cd1-x Te nanorods on graphene photodetector has been fabricated. The device shows vis-NIR broadband detection with high photoresponsivity (10 6 A/W).